Review of the Mexican species of Disholcaspis Dalla Torre & Kieffer with the description of eleven new species - Cuesta-Porta, Victor; Cooke-Mcewen, Crystal; Melika, George; Rangel, Silvia Romero-; Equihua-Martínez, Armando; Estrada-Venegas, Edith G.; Tapia, Ricardo Clark-; Serrano-Muñoz, Miriam; Chagoyán-García, Chrystian; Pujade-Villar, Juli (Zootaxa, 2024)
Disholcaspis Dalla Torre & Kieffer, 1910 is reviewed for the first time in Mexico. A total of 23 species have been studied, 12 previously known species, 11 new species, and one new synonym: D. brasoae Cuesta-Porta, sp. nov., D. callosa Pujade-Villar, Kinsey† & Cuesta-Porta, sp. nov., D. carpenteri Pujade-Villar, Cuesta-Porta & Melika, sp. nov., D. cinerosa (Bassett, 1881) (= D. pallens Kinsey, 1938 syn. nov.), D. cordifoliae Cuesta-Porta, Pujade-Villar & Kinsey†, sp. nov., D. crystalae Pujade-Villar, 2018, D. cummingi Pujade-Villar, Melika & Cuesta-Porta, sp. nov., D. familiaris Cuesta-Porta, sp. nov., D. hermesi Cuesta-Porta, Pujade-Villar & Melika, sp. nov., D. insulana Kinsey, 1938, D. laetae Kinsey, 1937, D. largior Kinsey, 1938, D. mexicana (Beutenmüller, 1911), D. nayeliae Cuesta-Porta, Melika & Pujade-Villar, sp. nov., D. potosina Kinsey, 1937, D. pulla Kinsey, 1937, D. punicea Pujade-Villar, Kinsey† & Cuesta-Porta, sp. nov., D. purlans Kinsey, 1937, D. purpurea Kinsey, 1937, D. puta Kinsey†, Cuesta-Porta & Pujade-Villar, sp. nov., D. raptor Pujade-Villar, Kinsey † & Cuesta-Porta, sp. nov., D. regina Kinsey, 1937, and D. unicolor Kinsey, 1920. We provide the descriptions of the new species, the re-descriptions of the previously known species, diagnoses and the first key to species for the Mexican Disholcaspis.